Correlação entre métodos de avaliação de maturação esquelética e dentária e marcadores bioquímicos de crescimento - Carelli, Julia (2019)
This study aimed to correlate skeletal and dental maturation evaluation methods, and also correlate with biochemical markers of growth. The sample consisted of 37 patients aged 10 to 16 years old who began orthodontic treatment to correct class II malocclusion. In the analysis of skeletal maturation were used methods of hand-wrist radiographs and analysis of cervical vertebrae. For hand-wrist radiographs the method used was described by Fishmann (1982) and in the analysis of cervical vertebrae the method of McNamara Jr. and Franchi (2018). The stage of dental development of those patients was also evaluated through panoramic projections obtained from tomographic sections. Two analyses were made: one according to Hofmann (2016) evaluating the third molar mineralization stage, and the other based on the method proposed by Demirjian (1973) where the seven mandibular teeth were observed. Finally, all patients underwent serological collections where the levels of IGF-1, Total Triiodothyronine-T3, Estradiol, Vitamin D, Estrone, Free Estriol, Growth HormoneHGH, Intact Parathyroid hormone-PTH and Testosterone were obtained. The data were analyzed by t-test and Mann-Whitney U. Pearson's correlation coefficient was used to determine the correlation strength between the variables. The statistical significance was p <0.05. According to the data obtained, the study found a strong correlation between skeletal maturation methods (p <0.0001; r = 0.864). Moderate correlation was observed between estradiol and maturational stage of cervical vertebrae and hand wrist radiograph (p = 0.043; r = 0.494 and r = 0.017; r = 0.056 respectively), testosterone also has a moderate correlation with maturational stage of cervical vertebrae and hand wrist radiograph in boys (r=0.559; p=0.019 e r= 0.636; p= 0.006 respectively). In girls, testosterone was moderately correlated with maturational stage of the cervical vertebrae (p = 0.104; r = 0.384). Chronological age presents a moderate correlation between dental maturity for both methods: Demirjian et al. (1973) (r = 0.564; p = 0.003) and method Hofmann et al. (2016) (r = 0.436; p = 0.011). Correlation between vitamin D and maturation indicators was not observed. In this study, a weak negative correlation was found between T3 and cervical vertebrae maturation stage (r = -0.396; p = 0.016). It is concluded that skeletal maturation evaluation methods are strongly correlated, estradiol and testosterone hormones are moderately correlated with skeletal maturation evaluation methods, and dental maturation evaluation methods are also moderately correlated.